Preparation method of lithium metal battery current collector

By preparing vertical channel Cu current collector in lithium metal batteries and using the Kirkendal effect to form a porous structure, the instability and safety hazards of lithium metal batteries are solved, and the cycle performance and service life of the battery are improved.

CN119297296AInactive Publication Date: 2025-01-10SHENZHEN QINGYAN HAOLONG NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411714073.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium metal batteries have application obstacles due to unstable solid electrolyte membranes, low Coulomb efficiency, safety hazards caused by dendrites' growth, severe volume expansion and large amounts of dead lithium.

Method used

The vertical channel Cu current collector is prepared by phase conversion method, and the porous current collector is prepared on it through the Kirkendal effect, which increases the deposition area of ​​lithium ions, reduces the current density, and uses the pores of the three-dimensional current collector to constrain unsupported lithium metal. Solve the above problems.

Benefits of technology

It significantly improves the cycling stability of lithium metal batteries, reduces charge accumulation, reduces current density, extends the service life of the battery, and reduces the uneven deposition and volume expansion of lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297296A_ABST
    Figure CN119297296A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of current collectors of lithium metal batteries, in particular to a preparation method of a current collector of a lithium metal battery, which comprises the following steps of: 1, preparing a vertical channel current collector by adopting a phase inversion method; and 2, preparing the vertical channel porous current collector by using the Kirkendall effect by taking the vertical porous current collector as a template. Through the Kirkendall effect, the mutual diffusion effect between two metal atoms with different diffusion rates and diffusion coefficients is achieved, and through long-term diffusion, a large number of Kirkendall holes can be formed in the contact surface of the two metals; the three-dimensional porous vertical current collector prepared by simply heating the diffusion couple has cavities which penetrate through the interior of the copper foil and are connected with each other, the three-dimensional porous vertical current collector has more advantages when being used as a current collector of a lithium metal battery, side reactions between lithium metal and electrolyte are greatly reduced, and the current density is also reduced due to the fact that the electrode area is increased for a three-dimensional structure of the three-dimensional porous vertical current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal battery current collector preparation, and in particular to a method for preparing a lithium metal battery current collector. Background Art

[0002] With the continuous progress of society and the vigorous development of science and technology, traditional fossil energy has become increasingly difficult to meet the growing energy demand. On the one hand, fossil energy is a non-renewable energy source and is difficult to use sustainably; on the other hand, the use of fossil energy will bring additional environmental problems, such as global warming and sea level rise caused by greenhouse gas production, and the emission of dust and harmful gases caused by incomplete combustion, causing air pollution, acid rain, etc. Therefore, the rational development and utilization of renewable resources including wind energy, hydropower, solar energy, geothermal energy, etc. can greatly improve the energy structure of today's society, alleviate climate change, and protect the ecological environment. It is an inevitable trend and important choice for solving energy problems. Therefore, the development of supporting energy storage technology is a necessary condition for the efficient use of non-fossil renewable energy. The development of efficient energy storage systems has become crucial for the centralized storage and utilization of electricity during the low-power period of renewable energy and traditional thermal power generation.

[0003] In the current commercial battery energy storage system, the energy density of lithium-ion batteries is higher than other battery systems, but the energy density of commercial lithium-ion batteries is still far lower than the energy density that fossil energy such as gasoline can provide. In addition, the rapid development of portable electronic devices such as laptops and mobile phones has also made the existing energy system face greater and greater challenges. It is urgent to develop the next generation of battery energy storage systems with intrinsic high energy density and high performance.

[0004] Unlike lithium-ion batteries, metals can be used independently as the negative electrode of the battery and paired with different types of positive electrode materials such as elemental sulfur and oxygen to provide the highest theoretical specific capacity (3860mAh / g), the lowest physical density (0.59g / cm 3 ) and the lowest electrochemical potential (-0.04V vs.SHE), therefore, lithium metal batteries have received unprecedented attention, and with the continuous development of rechargeable metal systems, the advantages of the lithium metal negative electrode itself have been gradually brought into play. It can be said that lithium metal batteries have the potential to replace the existing commercial battery system represented by lithium-ion batteries and shoulder important tasks in the next generation of energy storage systems. However, lithium metal batteries have strong irreversibility and inhomogeneity during deposition and stripping, which also brings many obstacles to the practical application of metal batteries. Among them, unstable solid electrolyte membranes and the side reactions they bring, low coulombic efficiency, safety hazards caused by dendrite growth, severe volume expansion and a large amount of dead lithium are common and prominent problems faced in the practical application of metal batteries.

[0005] To this end, the inventors in this field proposed a method for preparing a lithium metal battery current collector, using a phase inversion method to prepare a vertical channel Cu current collector, and then using the Kirkendall effect to prepare a porous current collector on the vertical channel current collector, increasing the deposition area of ​​lithium ions and reducing the current density, and the pores of the three-dimensional current collector can constrain the unsupported lithium metal. In this way, the unstable solid electrolyte membrane of lithium metal batteries and the side reactions it brings, low coulomb efficiency, safety hazards caused by dendrite growth, severe volume expansion, and a large amount of dead lithium can be solved. Summary of the invention

[0006] Technical problems to be solved: The unstable solid electrolyte membrane of lithium metal batteries and the side reactions it brings, low Coulomb efficiency, safety hazards caused by dendrite growth, serious volume expansion and a large amount of dead lithium.

[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing a lithium metal battery current collector, thereby solving the technical problems mentioned in the background technology.

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A method for preparing a lithium metal battery current collector comprises the following steps:

[0010] Step 1: Prepare a vertical channel current collector by a phase inversion method;

[0011] Step 2: Using the vertical porous current collector as a template, a vertical channel porous current collector is prepared using the Kirkendall effect.

[0012] In a possible implementation, the steps of preparing the vertical channel current collector are as follows:

[0013] Step 1.1: Prepare four raw materials: graphite, polyethersulfone (PESF), polyvinylpyrrolidone (PVP), and copper oxide (CuO) powder;

[0014] Step 1.2: Graphite, polyethersulfone (PESF) and polyvinylpyrrolidone (PVP) are mixed in a certain proportion, ball-milled for a period of time, and then a solvent is added and ball-milled again to obtain a template slurry;

[0015] Step 1.3: copper oxide (CuO) powder, polyethersulfone (PESF) and polyvinylpyrrolidone (PVP) are mixed in a certain proportion, ball-milled for a period of time, and then a solvent is added and ball-milled to obtain a base slurry;

[0016] Step 1.4: Mix the two slurries according to the proportion and then ball-mill again to obtain a uniform and viscous liquid slurry;

[0017] Step 1.5: Use double-layer casting to cast the two slurries onto the PET carrier film;

[0018] Step 1.6: Transfer the PET carrier film to deionized water for immersion to complete the phase inversion process and form a green embryo;

[0019] Step 1.7: After the embryo is taken out and dried and calcined, the vertical channel current collector can be obtained.

[0020] In a possible implementation, in step 1.5, the graphite template slurry is located in the lower layer to serve as a sacrificial layer, and the copper oxide (CuO) base slurry is located in the upper layer.

[0021] In one possible implementation, in step 1.7, the green embryo after drying needs to be calcined twice. The first calcination is carried out in a muffle furnace to remove carbon for completely removing the template layer. The second calcination is to transfer the base layer to a tubular furnace and calcine it in an argon atmosphere to obtain a vertical channel current collector.

[0022] In a possible implementation manner, the solvent is NMP (N-methyl-2-pyrrolidone) solvent.

[0023] In a possible implementation, the steps for preparing the vertical channel porous current collector are as follows:

[0024] Step 2.1: Prepare five raw materials: carboxymethyl cellulose (CMC), deionized water, tin (Sn) powder, gallium (Ga) powder, and aluminum (Al) powder;

[0025] Step 2.2: adding carboxymethyl cellulose (CMC) to a certain amount of deionized water and stirring to obtain a CMC solution;

[0026] Step 2.3: Mix and stir metal powders of tin (Sn), gallium (Ga), and aluminum (Al) with the CMC solution to obtain a stable slurry;

[0027] Step 2.4: The slurry is coated on the vertical channel current collector cleaned with alcohol to prepare a diffusion couple composed of copper and different metals;

[0028] Step 2.5: heating the vertical channel current collector coated with metal powder to accelerate the interdiffusion between copper and other metals;

[0029] Step 2.6: Remove the remaining metal powder slurry on the vertical channel current collector to obtain a porous three-dimensional vertical current collector.

[0030] In a possible implementation, the vertical channel current collector coated with metal powder needs to be heated three times in total, and the three heating temperatures are 120° C., 200° C., and 500° C., respectively, and the heating time is 10 hours respectively.

[0031] In a possible implementation, the metal powder slurry remaining on the vertical channel current collector needs to be cleaned with dilute hydrochloric acid liquid.

[0032] Beneficial effects compared with the prior art:

[0033] 1. The present invention provides a method for preparing a three-dimensional porous vertical current collector. This vertical channel structure can accommodate the volume change of lithium during the cycle and significantly reduce the local current density, avoid charge accumulation, and is conducive to the uniformity of lithium deposition;

[0034] 2. The present invention proposes an environmentally friendly method for preparing a three-dimensional porous copper current collector. The Kirkendall effect is the mutual diffusion effect between two metal atoms with different diffusion rates and diffusion coefficients. After long-term diffusion, a large number of Kirkendall holes will be formed on the contact surface of the two metals. The three-dimensional porous vertical current collector prepared by simple heating diffusion has holes that penetrate the interior of the copper foil and are interconnected. It has more advantages as a current collector for lithium metal batteries. The side reaction between lithium metal and electrolyte is greatly reduced, and the current density is also reduced because its three-dimensional structure increases the electrode area;

[0035] 3. The present invention uses two lithium-philic atoms, aluminum (Al) and gallium (Ga), to form diffusion couples on the current collector, which can increase the electrode area and provide more lithium ion deposition sites, thereby improving the capacity of the battery. At the same time, the alloy formed by the lithium-philic element and lithium can be used as an effective lithium ion source, further promoting the uniform deposition of lithium, reducing the volume expansion and stress concentration of the battery during the cycle process, thereby extending the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.

[0037] Figure 1 Schematic diagram of the preparation steps of a lithium metal battery current collector. DETAILED DESCRIPTION

[0038] Preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. However, the present invention can also be implemented in various forms, so the present invention is not limited to the embodiments described below.

[0039] The technical solution in the embodiment of the present application is to solve the problems of the above-mentioned background technology, and the overall idea is as follows:

[0040] Embodiment 1:

[0041] The preparation method of the porous three-dimensional vertical current collector material of this embodiment is as follows:

[0042] Step 1, preparing a vertical channel copper (Cu) current collector;

[0043] Step 1.1, preparing graphite, polyethersulfone (PESF), polyvinylpyrrolidone (PVP), and copper oxide (CuO) powders;

[0044] Step 1.2: 10 g of graphite, 3 g of polyethersulfone (PESF), and 1.5 g of polyvinylpyrrolidone (PVP) were mixed and ball-milled on a planetary ball mill for 30 min, and then an appropriate amount of NMP (N-methyl-2-pyrrolidone) solvent was added and the ball-milling was continued for 2 h to obtain a template slurry;

[0045] Step 1.3, take 10g of copper oxide (CuO) powder, 3g of polyethersulfone (PESF), and 1.5g of polyvinylpyrrolidone (PVP), mix them, and ball-mill them on a planetary ball mill for 30min, then add an appropriate amount of NMP (N-methyl-2-pyrrolidone) solvent and continue ball-milling for 2h to obtain a current collector substrate slurry;

[0046] Step 1.4: Mix the two slurries in a mass ratio of 1:1 and perform ball milling on a planetary ball mill for 2 hours to obtain a uniform viscous liquid slurry.

[0047] Step 1.5, using double-layer casting to cast the two slurries together onto the PET carrier film, wherein the graphite template slurry is located at the lower layer as a sacrificial layer, and the copper oxide (CuO) current collector substrate slurry is located at the upper layer;

[0048] Step 1.6, quickly transfer it to deionized water and soak it for 6 hours, and after the phase transformation is completed, a green embryo is formed;

[0049] Step 1.7, take out the embryo body and dry it in a vacuum drying oven at 80°C for 10 hours. After drying, a dry embryo body is obtained. The dry embryo body is then placed in a muffle furnace and kept at 800°C for 4 hours under an argon atmosphere to remove carbon. After the template layer is completely removed, it is transferred to a tubular furnace and kept at 800°C for 4 hours under an argon atmosphere. It is cooled to room temperature with the furnace to obtain a vertical channel Cu current collector;

[0050] Step 2, preparing a porous three-dimensional vertical current collector;

[0051] Step 2.1: Prepare five raw materials: carboxymethyl cellulose (CMC), deionized water, tin (Sn) powder, gallium (Ga) powder, and aluminum (Al) powder.

[0052] Step 2.2, take 10g of carboxymethyl cellulose (CMC), add a certain amount of deionized water and continue stirring to prepare a CMC solution with a mass fraction of 1.5%;

[0053] Step 2.3, take 5g aluminum chloride (AlCl3) and 5g gallium chloride (GaCl3) metal powder, add them into CMC solution and stir for 24h to prepare a stable slurry.

[0054] Step 2.4, coating the slurry on a vertical channel current collector with a thickness of 8 μm to a coating thickness of 30 μm to prepare a diffusion couple composed of copper and different metals;

[0055] Step 2.5, heating the vertical channel current collector coated with metal powder at 120° C., 200° C., and 500° C. for 10 h respectively to accelerate the diffusion between copper and other metals;

[0056] Step 2.6, after the heating is completed, the remaining metal powder slurry on the vertical channel current collector is cleaned with dilute hydrochloric acid to obtain a porous three-dimensional vertical current collector;

[0057] Step 3: Cut the porous three-dimensional vertical current collector into a disc with a diameter of 12 mm as the working electrode, use the lithium sheet as the counter electrode, and assemble it into a 2025 button battery with a double-sided ceramic diaphragm and a lithium metal electrolyte.

[0058] The battery was tested for gram capacity and cycle performance, and the tested specific capacity was 30mAh / cm2.

[0059] Embodiment 2:

[0060] The preparation method of the vertical channel copper (Cu) current collector material of this embodiment is as follows:

[0061] Step 1, preparing a vertical channel copper (Cu) current collector;

[0062] Step 1.1, preparing graphite, polyethersulfone (PESF), polyvinylpyrrolidone (PVP), and copper oxide (CuO) powders;

[0063] Step 1.2: 10 g of graphite, 3 g of polyethersulfone (PESF), and 1.5 g of polyvinylpyrrolidone (PVP) were mixed and ball-milled on a planetary ball mill for 30 min, and then an appropriate amount of NMP (N-methyl-2-pyrrolidone) solvent was added and the ball-milling was continued for 2 h to obtain a template slurry;

[0064] Step 1.3, take 10g of copper oxide (CuO) powder, 3g of polyethersulfone (PESF), and 1.5g of polyvinylpyrrolidone (PVP), mix them, and ball-mill them on a planetary ball mill for 30min, then add an appropriate amount of NMP (N-methyl-2-pyrrolidone) solvent and continue ball-milling for 2h to obtain a current collector substrate slurry;

[0065] Step 1.4: Mix the two slurries in a mass ratio of 1:1 and perform ball milling on a planetary ball mill for 2 hours to obtain a uniform viscous liquid slurry.

[0066] Step 1.5, using double-layer casting to cast the two slurries together onto the PET carrier film, wherein the graphite template slurry is located at the lower layer as a sacrificial layer, and the copper oxide (CuO) current collector substrate slurry is located at the upper layer;

[0067] Step 1.6, quickly transfer it to deionized water and soak it for 6 hours, and after the phase transformation is completed, a green embryo is formed;

[0068] Step 1.7, take out the embryo body and dry it in a vacuum drying oven at 80°C for 10 hours. After drying, a dry embryo body is obtained. The dry embryo body is then placed in a muffle furnace and kept at 800°C for 4 hours under an argon atmosphere to remove carbon. After the template layer is completely removed, it is transferred to a tubular furnace and kept at 800°C for 4 hours under an argon atmosphere. It is cooled to room temperature with the furnace to obtain a vertical channel Cu current collector;

[0069] Step 2: Cut the vertical channel Cu current collector into a disc with a diameter of 12 mm as the working electrode, use the lithium sheet as the counter electrode, and assemble it into a 2025 button cell with a double-sided ceramic diaphragm and a lithium metal electrolyte.

[0070] The battery was tested for gram capacity and cycle performance, and the tested specific capacity was 30mAh / cm2

[0071] Embodiment 3:

[0072] The preparation method of the porous copper current collector material of this embodiment is as follows:

[0073] Step 1, preparing a porous current collector;

[0074] Step 1.1, take 10g carboxymethyl cellulose (CMC), add a certain amount of deionized water and continue stirring to prepare a mixed solution with a mass fraction of 1.5%, take 5g aluminum chloride (AlCl3) and 5g gallium chloride (GaCl3) metal powder and add the carboxymethyl cellulose (CMC) solution in turn and stir for 24h to prepare a stable slurry. Subsequently, the slurry is coated on a copper foil with a thickness of 8μm, and the coating thickness is 30μm to prepare a diffusion couple composed of copper and different metals.

[0075] Step 1.2, heating the copper current collector coated with metal powder at 120° C., 200° C., and 500° C. for 10 hours respectively to accelerate the diffusion between copper and other metals. After the heating is completed, the remaining metal powder slurry on the vertical channel current collector is washed with dilute hydrochloric acid to obtain a porous copper current collector;

[0076] Step 1.3, cut the porous current collector into a disc with a diameter of 12 mm as the working electrode, use the lithium sheet as the counter electrode, and assemble it into a 2025 button battery with a double-sided ceramic diaphragm and a lithium metal electrolyte.

[0077] Step 2: The nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material is cut into a disc with a diameter of 12 mm as a working electrode, and a lithium sheet is used as a counter electrode and assembled with a ceramic diaphragm and a lithium metal electrolyte to form a 2025 button battery.

[0078] The battery was tested for cycle performance, and the specific capacity was 30mAh / cm2.

[0079] Experimental example:

[0080] The test temperature is 25°C, and the test voltage range is 2.8 to 4.3.5V. Examples 1-3 are connected to a charging cabinet, first charged to 2.8V with a 0.1C constant current, allowed to stand for 5 minutes, then charged to 4.35V with a 0.1C constant current, allowed to stand for 5 minutes, this step is repeated twice, and then allowed to stand for 30 minutes to complete the step; discharged to 2.8V with a 0.5C constant current, allowed to stand for 5 minutes, then charged to 4.35V with a 0.3C constant current, allowed to stand for 5 minutes, and this step is repeated until the battery capacity retention rate is 80%, and the tested specific capacity is 30mAh / cm2.

[0081] The following table shows the gram capacity of the vertical channel current collector of Examples 1-3 for lithium sheet buckle and battery cycle performance:

[0082] Example Number of cycles Example 1 258 Example 2 199 Example 3 152

[0083] It can be seen that the modified vertical channel current collector can accommodate the volume change of lithium during the cycle and reduce the local current density due to its special pore structure, avoid charge accumulation, and allow lithium to be evenly deposited on the copper foil, thereby improving the cycle stability of the lithium metal battery.

[0084] The pore modification carried out on this basis further increases the electrode area, and the two elements that form the diffusion couple are lithium-philic elements, which can form alloys with lithium elements, reduce the ion nucleation barrier, help ion dynamics, and improve its capacity.

[0085] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium metal battery current collector, characterized in that: The following steps are involved: Step 1: Prepare a vertical channel current collector by a phase inversion method; Step 2: Using the vertical porous current collector as a template, a vertical channel porous current collector is prepared using the Kirkendall effect.

2. The method for preparing a lithium metal battery current collector according to claim 1, characterized in that: The steps for preparing the vertical channel current collector are as follows: Step 1.1: Prepare four raw materials: graphite, polyethersulfone (PESF), polyvinylpyrrolidone (PVP), and copper oxide (CuO) powder; Step 1.2: Graphite, polyethersulfone (PESF) and polyvinylpyrrolidone (PVP) are mixed in a certain proportion, ball-milled for a period of time, and then a solvent is added and ball-milled again to obtain a template slurry; Step 1.3: copper oxide (CuO) powder, polyethersulfone (PESF) and polyvinylpyrrolidone (PVP) are mixed in a certain proportion, ball-milled for a period of time, and then a solvent is added and ball-milled to obtain a base slurry; Step 1.4: Mix the two slurries according to the proportion and then ball-mill again to obtain a uniform and viscous liquid slurry; Step 1.5: Use double-layer casting to cast the two slurries onto the PET carrier film; Step 1.6: Transfer the PET carrier film to deionized water for immersion to complete the phase inversion process and form a green embryo; Step 1.7: After the embryo is taken out and dried and calcined, the vertical channel current collector can be obtained.

3. The method for preparing a lithium metal battery current collector according to claim 2, characterized in that: In the step 1.5, the graphite template slurry is located at the lower layer to serve as a sacrificial layer, and the copper oxide (CuO) base slurry is located at the upper layer.

4. The method for preparing a lithium metal battery current collector according to claim 2, characterized in that: In the step 1.7, the green embryo needs to be calcined twice after drying. The first calcination is carried out in a muffle furnace to remove carbon for completely removing the template layer. The second calcination is to transfer the base layer to a tubular furnace and calcine it in an argon atmosphere to obtain a vertical channel current collector.

5. The method for preparing a lithium metal battery current collector according to claim 2, characterized in that: The solvent used is NMP (N-methyl-2-pyrrolidone) solvent.

6. The method for preparing a lithium metal battery current collector according to claim 1, characterized in that: The steps for preparing the vertical channel porous current collector are as follows: Step 2.1: Prepare five raw materials: carboxymethyl cellulose (CMC), deionized water, tin (Sn) powder, gallium (Ga) powder, and aluminum (Al) powder; Step 2.2: adding carboxymethyl cellulose (CMC) to a certain amount of deionized water and stirring to obtain a CMC solution; Step 2.3: mixing and stirring metal powders of tin (Sn), gallium (Ga), and aluminum (Al) with a carboxymethyl cellulose (CMC) solution to obtain a stable slurry; Step 2.4: The slurry is coated on the vertical channel current collector cleaned with alcohol to prepare a diffusion couple composed of copper and different metals; Step 2.5: heating the vertical channel current collector coated with metal powder to accelerate the interdiffusion between copper and other metals; Step 2.6: Remove the remaining metal powder slurry on the vertical channel current collector to obtain a porous three-dimensional vertical current collector.

7. The method for preparing a lithium metal battery current collector according to claim 6, characterized in that: The vertical channel current collector coated with metal powder needs to be heated three times in total, and the three heating temperatures are 120° C., 200° C., and 500° C., respectively, and the heating time is 10 hours respectively.

8. The method for preparing a lithium metal battery current collector according to claim 6, characterized in that: The remaining metal powder slurry on the vertical channel current collector needs to be cleaned with dilute hydrochloric acid liquid.

Citation Information

Patent Citations

  • Porous metal and preparation method thereof

    CN105648255A

  • Three-dimensional porous current collector prepared based on diffusion couple and preparation method and application thereof

    CN110504454A

  • Compressible flexible air electrode current collector with honeycomb structure and preparation method thereof

    CN115939436A